Sober mom, healthy baby? Effects of brief alcohol interventions in Swedish maternity care - Erik Grönqvist; Anna Norén; Anna Sjögren; Helena Svaleryd (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
A large body of research documents the importance of early life conditions for the health and human capital formation of children. The detrimental effects of alcohol exposure in utero are well documented, and therefore identifying effective methods for preventing harmful maternal alcohol consumption is of great importance. We exploit the stepwise introduction of alcohol screening and brief interventions at Swedish antenatal clinics, to evaluate the causal effect of enhanced alcohol prevention on infant health using a difference-in-differences strategy. We find that the program improves infant health measured by prescription of pharmaceutical drugs and hospitalizations during the child's first year of life. The results suggest that effects are likely driven by changes in maternal behavior after the first trimester and seem to extend beyond the birth of the child.
Keywords: I12; I18; 330; alcohol prevention; Brief intervention; AUDIT; Antenatal care; Child health